Three new records of the genus Lutzomyia of the subgenus Helcocyrtomyia (Diptera: Psychodidae: Phlebotominae) from Southwestern Brazilian Amazonia - Ortiz, Dennys Ghenry Samillan; Pinto, Mara Cristina [UNESP]; Cesario, Manuel; Galati, Eunice Aparecida Bianchi; Molina, Silvia Maria Guerra; Borges, Diones Antonio (Elsevier, 2019)
The sand fly phlebotomine fauna of the Brazilian municipality of Assis Brasil, Acre was sampled between April 2013 and March 2014 using modified CDC light traps. A total of 22,334 sand flies were collected, 41 of them belonging to three species: Lutzomyia gonzaloi, Lu. kirigetiensis and Lu. munaypata, of the subgenus Helcocyrtomyia, which have previously only been recorded in Peru. This paper presents their first reported collection in Brazil.
Keywords: Acre; Assis Brasil; Entomology; Osornoi series; Sanguinaria series